Outpatient antipsychotic drug use in children and adolescents in Germany between 2004 and 2011 - Schröder, Carsten; Dittmann, Ralf (European child & adolescent psychiatry, 2016)
Studies from different countries showed increasing use of antipsychotics in pediatric patients. However, these studies were methodologically limited and could not assess underlying diagnoses and off-label use sufficiently. This is the first study to examine antipsychotic prescriptions in a representative sample of minors over a long period, looking at changes regarding substances and drug classes, underlying diagnoses, and the rate of off-label use. Claims data of about two million pediatric subjects were used to calculate annual prevalences and incidence rates of antipsychotic prescriptions for the years 2004-2011. Analyses were stratified by sex, age, and drug type. Numbers of prescriptions, frequencies of diseases/disorders, the prescribing physicians’ specialties, and the share of off-label prescriptions were examined. During the study period, the prevalence of antipsychotic prescriptions ranged between 2.0 and 2.6 per 1000 minors. Antipsychotic prescriptions in children younger than 6 years decreased from 2.42 per 1000 subjects in 2004 to 0.48 in 2011. Among antipsychotic users, 47.0 % had only one prescription and hyperkinetic disorder was, by far, the most frequent diagnosis. The annual share of off-label prescriptions varied between 61.0 and 69.5 %. Antipsychotics were mainly prescribed to manage aggressive and impulsive behaviors in hyperkinetic disorder patients. This explains the high share of off-label prescriptions but raises concerns, since efficacy and safety of antipsychotics in this indication have not been sufficiently investigated. The decreasing antipsychotic use in younger children and the high proportion of antipsychotic users with one-time prescriptions are striking and should be further investigated in the future.